South Korea's Trade Diplomacy Strategy towards the Netherlands in Dealing with Japan's Semiconductor Raw Material Protection Policy during 2019-2022: English - Hafizhah Aushafi; Dadan Suryadipura (Global Local Interactions: Journal of International Relations, 2023)
The objective of this study was to elucidate South Korea's trade diplomacyendeavors in augmenting trade and investment in the Netherlands during the timeframe of 2019-2022. The author employs the notions of economic diplomacy and trade diplomacy from the Okano-Heijmans conceptual framework to elucidate the essence of the research. During the 2019-2022 timeframe, South Korea has implemented trade diplomacy efforts aimed at enhancing its potential to export products, particularly semiconductors. The implementation of a safeguard policy for Japanese semiconductor raw materials is a response to constraints in the availability of raw materials, as well as the trade conflict between the United States and China, which has repercussions for South Korea's trade ties with Japan. To enhance exports, the South Korean government is implementing several trade diplomacy initiatives, including engaging in commerce through Foreign Trade Agreements and promoting investment through bilateral relations focused on both government and private sector involvement, particularly with the Netherlands. In addition, South Korean representatives visited ASML, a Dutch company that manufactures semiconductor production machinery. Nevertheless, South Korea must confront some obstacles in order to succeed in the semiconductor trade battle, particularly the imperative for quality advancement. In this paper, the author will also explore the investment prospects of South Korea for the Netherlands.